Motivation and impostor syndrome as factors of professional burnout - YABLONSKA, Tetiana; SHEVCHUK, Anastasia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The problem of professional burnout in the modern world is becoming increasingly relevant due to the growing intensity of work and high demands on specialists. Among the factors of burnout, a special place is occupied by motivational aspects and internal psychological barriers, such as imposter syndrome. The desire for professional growth is a natural driving force, but in combination with doubts in one`s own abilities, it can lead to emotional and physical exhaustion. The aim of this article is to clarify the features of motivation and the impostor syndrome as factors contributing to professional burnout among specialists. Methods. The empirical study used: “Spilberger-Khanin Anxiety Questionnaire” (Khanina Yu. L.), P. Klans Impostor Phenomenon Scale (adapted by Shevchuk A., Yablonska T.), V. Schaufeli “Vitality Check” Questionnaire (adapted by Karamushki L.), Connor-Davidson-10 Resilience Scale (adapted by Kireeva Z., Odnostalko O., Biron B.), Professional Vitality Questionnaire (Kokun, 2021-b), Mental Health Stability – Short Form (adapted by Nosenko E., Chetvertyk-Burchak A.), Professional Burnout Diagnostics (MBI-HSS, UIKPT). The Jamovi 2.3.28 statistical package was used to analyze the data. The descriptive statistics method, Kolmogorov–Smirnov criteria, Mann–Whitney and Kruskal–Wallis U-criterion, Spearman correlation coefficient were used. The sample consisted of 274 individuals over 18 years of age, of whom 82.8% were women and 17.2% were men. Results. Moderate levels of professional burnout, anxiety, impostor syndrome, professional resilience, and mental health stability were revealed, as well as an above-average level of resilience. Direct relationships between personal anxiety, perfectionism, resilience, and impostor syndrome were statistically confirmed. Based on regression analysis, a statistically significant model was obtained that explains 33.6% of the variance in data on professional burnout. According to the model, the predictors of professional burnout are perfectionism, anxiety, the motivational component of professional resilience, and imposter syndrome. In contrast, perfectionism has the strongest direct positive effect on the level of burnout. Conclusions. It was found that personal anxiety, perfectionism, resilience, and imposter syndrome are factors of professional burnout. The hypothesis that professional burnout is more severe in adolescence, which is associated with difficulties in professional formation, unstable motivation, and manifestations of imposter syndrome in young specialists, is confirmed.